Analysis of body color formation of leopard coral grouper Plectropomus leopardus - Hao, Ruijuan; Zhu, Xiaowen; Tian, Changxu; Zhu, Chunhua; Li, Guangli (Frontiers in Marine Science, 2022)
Body color is an essential ecological phenotypic trait determining the ability of aquatic animals to adapt to or survive in a treacherous environment. However, researches regarding its underlying molecular mechanism in leopard coral groupers has been limited. Therefore, mRNAs, metabolites, and miRNAs of different-colored leopard coral grouper (Plectropomus leopardus) were sequenced to investigate the body color formation mechanism. The transcriptome analysis identified 1236 genes as differentially expressed genes (DEGs), of which 579 were up-regulated and 657 were down-regulated in the red-colored group compared with the brown-colored group (FDR < 0.01 and |log2FC| > 1). Metabolome analysis revealed 439 and 84 SDMs in POS and NEG of liquid chromatography-mass spectrometry, respectively (VIP > 1 and P < 0.05). The miRNA analysis exhibited 149 (120 up-regulated and 29 down-regulated) differentially expressed miRNAs (DEMs) in the analysis of the brown-colored vs. red-colored groups (P < 0.05 and |log2FC| > 1), including miR-144, miR-185, miR-192, miR-2188, miR-6316, novel-m0015, and novel-m0040. Integrated analysis of multiple omics exhibited that carotenoid metabolism, immune response, lipid metabolism, and amino acid metabolism were involved in the body color formation and adaptation to the environment. Therefore, the present multiomics research prepared a foundation for bright body color formation and promoted the process of preferred body-color breeding.